XX ÁSIRDIŃ 20-30-JÍLLARÍNDA QARAQALPAQSTANDA KITAPXANAShÍLÍQ ISIN RAWAJLANDÍRÍWDA XALÍQ ZIYALÍLARÍNÍŃ ORNÍ - Reymbaev, Rustem Sarsenbaevich (SCIENCE and SOCIETY, 2026)
The article highlights the field of librarianship in Karakalpakstan, the activities of cultural and educational institutions, the tasks of eliminating illiteracy, the role of the intellectual elite in the development of librarianship, and the role of Soviet party resolutions in this area during the period of cultural restructuring.